A SHORT REVIEW ON IMPORTANCE OF NIDRA SLEEP IN AYURVEDA - Jadhav, Dnyaneshwar; Bhaisare, Gautam jagdish (International Journal of Research -GRANTHAALAYAH, 2025)
In Ayurveda, Nidra (sleep) is described as one of the three pillars of life. Ahara (diet) and Brahmacharya (regulated lifestyle) and nidra (sleep) three pillars called as Trayopastambha. Proper Nidra plays a important role in maintaining physical as well as mental well-being. During sleep, the body undergoes repair and rejuvenation process. Proper sleep nourishes the dhatus (tissues), enhances strength (bala), supports immunity (ojas), and restores energy lost during the day. Sleep play major role in the balance of the three doshas also. Nidra is equally important for mental health also. It improves concentration, memory, and decision-making ability, calming stress. Proper Nidra improve skin complexion that’s why, nidra is often called a “Natural cosmetic.” Disturbances in sleep lead to many disorders. Thus, Nidra is not only rest but a restorative process essential for physical and mental health, immunity.